ANALYSIS OF DETERMINANTS INFLUENCING PREMIUM PRICING OF GUEST HOUSES IN WEST DENPASAR, BALI - Eko Wahyudi; David Sukardi Kodrat; Eric Harianto; Yuli Kartika Dewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to test the hypothesis regarding the variables that form premium pricing for guesthouses in West Denpasar, Bali. The theories applied in this research are service marketing theory, with an in-depth analysis of the Flower of Services and Shostack’s Molecular Model. The study employs Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Data was collected through the distribution of structured questionnaires. The population of this study consists of visitors to Andakasa Residence guesthouse during the 2022-2023 period, totaling 178 individuals. The sample size was 124 respondents, determined through probability sampling using the simple random sampling technique with a 5% margin of error. The results indicate that the indicators Information, Hospitality, Safekeeping, Exceptions, Essential Evidence, Distribution Strategy, Pricing Strategy, and Service Elements contribute to premium pricing. In contrast, Order Taking, Billing, Payment, Consultation, Advertising Strategy, and Product Elements do not form premium pricing for guesthouses in West Denpasar, Bali. It is hoped that these findings can provide insights for guesthouse owners in West Denpasar, particularly Andakasa Residence, to improve their services and establish premium pricing based on the variables examined in this study.